(899) النماذج الرياضية لتخطيط الإنتاج والتخزين Mathematical Models for Production and Inventory Planning. - مكارى, نادية (2024)
تهدف هذه الدراسة إلى تحليل وتقييم نماذج التخزين المختلفة المستخدمة في إدارة المخزون، مع التركيز على نماذج التخزين ذات الطلب المحدد والعشوائي. تتناول الدراسة آليات تطبيق هذه النماذج في بيئات الأعمال المختلفة وتناقش تأثيرها على تقليل التكاليف وزيادة الكفاءة التشغيلية. بالإضافة إلى ذلك، تم تقديم ملاحق رياضية لدعم النماذج المقدمة وتوضيح الجوانب الحسابية المرتبطة بها. توصلت الدراسة إلى أن اختيار النموذج المناسب يعتمد على طبيعة الطلب ومستوى التغير في السوق، مع ضرورة اعتماد استراتيجيات مرنة لمواجهة التحديات المتغيرة. / / This study aims to analyze and evaluate various storage models used in inventory management, focusing on demand-determined and random-demand models. It explores the implementation mechanisms of these models in different business environments and discusses their impact on cost reduction and operational efficiency. Additionally, mathematical appendices were provided to support the proposed models and clarify their computational aspects. The study concludes that selecting the appropriate model depends on the nature of demand and market fluctuations, emphasizing the importance of adopting flexible strategies to address dynamic challenges.